Sildenafil citrate therapy for IUGR and its effect on umbilical artery Doppler - Abdel A.G.E.-; Mahmoud A Badawy; Sally M.G Farghaly (Wolters Kluwer Medknow Publications, 2020)
Background Intrauterine growth restriction (IUGR) occurs when there is deficiency of gas exchange and nutrient delivery to the fetus not allowing it to thrive in utero. This happens because of maternal diseases that decrease oxygen-carrying capacity (e.g. cyanotic heart disease, smoking, and hemoglobinopathy) or by maternal vascular diseases causing a dysfunctional oxygen delivery system or idiopathic causes. Sildenafil (phosphodiesterase-5) inhibitor consists of the citrate salt of sildenafil; it is a selective and specific inhibitor of cyclic guanosine monophosphate. It is primarily used for sexual dysfunction, antidepressant-associated sexual dysfunction, pulmonary hypertension, altitude thickness, and Raynaud's phenomenon. Herein, the trial is used for improving uteroplacental perfusion by enhancing vasodilatation of myometrial small artery, decreasing peripheral resistance, and boosting flow within the uteroplacental bed. Aim The aim was to evaluate efficacy and role of sildenafil citrate on the blood flow of uteroplacental circulation and fetal growth in pregnancies accompanied by fetal growth restriction because of dysfunctional oxygen delivery system guided by umbilical Doppler ultrasound. Patients and methods Our study was a prospective double-blind, randomized, controlled trial. The patients were recruited from women with IUGR attending the emergency ward and outpatient clinic at Sohag teaching Hospital. The study comparing three groups of 150 women. Each group consisted of 50 women. One group received 20 mg of sildenafil citrate orally twice/day, the second received a dose of 40 mg every 12 h vaginally, whereas the last one received a placebo, as a control group. Results After treatment, improvement of Doppler in the form of S/D, resistance index, and pulsatility index showed highly significant difference between the two sildenafil groups compared with the control one. Conclusion Sildenafil therapy may offer a new breakthrough in treatment of IUGR-complicated pregnancies, with improvement of the perinatal outcomes.